The Eurocentric Colonialist Discourse of the Centroamerican Elites in the Context of the Paris, Madrid, Chicago and Guatemala World Fairs in the XIX Century - Cubero Barrantes, Guillermo (Revista de historia., 2019)
The present article refers to the theoretical methodological apparatus related to the problem in the reproduction of the Eurocentric colonialist discourse of the Central American elites in the context of the Great Universal Exhibitions of the XIX century. This reproduction produced a series of topics, tensions and discursive tendencies that affected, and continue to do so in the present, in the relations of economic, social and political disadvantage of the Central American Isthmus in relation to the western North Atlantic Powers.